PENGARUH PENERAPAN PENDEKATAN BRAIN BASED LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMAN 12 PADANG - Ade Silvia Yeni (PILLAR OF PHYSICS EDUCATION, 2014)
The one direction of learning process made students less participated in class. Less communication between teachers and students also made them affraid to conveyed their own opinion. This condition made the weaknesses of the students  ability in thingking that impact on low marked of their result. One way to improve their result in learning was using Brain Based Learning approached which supposed to optimalize the worked of their brain, so that the learning process become meaningfull. The purpose of this study was to investigate the effect of applying the Brain Based Learning approach to the result of learning physics of class X in SMAN12 Padang. The type of research conducted by the quasi- experimental research design used is " Randomized Control Group Design Only ". The population were all of class X students enrolled in Academic Year 2013/2014. The sample taken by using technique cluster random sampling. The experimental class and control class determined at random. The research data includes learning outcomes in three domains , namely cognitive, affective , and psychomotor domains. Assessment instruments is used written test for cognitive, affective observation sheets for affective and rubrics for scoring for psychomotor domain . The research data were analyzed using two similarity test average of the t test with a significance level of 0,05. The results of the analysis of the data shows the average value of the experimental class on cognitive, affective and psychomotor domain higher than control class. Based on the results of the study concluded that there is a significant effect of the application of Brain Based Learning approach to physics learning outcomes in the cognitive, affective and psychomotor domains class X students of SMAN 12 Padang